Geopolymer / silver disilicate photocatalyst, heterojunction photocatalyst, 3D configuration photocatalyst, preparation method and application thereof
The preparation of geological polymer/silver pyrosilicate photocatalysts by co-precipitation method solves the problem of photocorrosion and single structure of silver pyrosilicate photocatalysts, and achieves the effect of improving their photocatalytic performance and recovery efficiency.
Patent Information
- Application Number
- CN202410189328.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-02-20
AI Technical Summary
The existing silver pyrosilicate photocatalysts are susceptible to photocorrosion, resulting in their performance being unable to be fully utilized. At the same time, their structure is single and easy to agglomerate, and their recycling is difficult, which limits their promotion and application in the field of energy and environment.
By mixing the alkali with the silica sol to form an alkali excitation liquid, then co-precipitated with the aluminosilicate material and silver nitrate, a geological polymer/silver pyrosilicate photocatalyst was prepared. This method not only improves the photocatalytic properties of silver pyrosilicate, but also improves its structure and recovery efficiency through composite geological polymers.
The service stability and catalytic performance of silver pyrosilicate photocatalysts have been improved, their structure and recycling efficiency have been improved, and their application potential in the field of energy and environment are enhanced.
Smart Images

Figure CN117943129B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysts, and in particular to geopolymer / silver disilicate photocatalysts, heterojunction photocatalysts, 3D configuration photocatalysts, and preparation methods and applications thereof. Background Art
[0002] Geopolymer is a type of amorphous / semi-crystalline inorganic polymer with silicon-oxygen tetrahedron ([SiO4]) and aluminum-oxygen tetrahedron ([AlO4]) as basic structural units, which is formed by alkali-activated aluminum silicate raw materials (metakaolin, fly ash or slag) using active ingredients such as K2SiO3 and Na2SiO3, and then undergoing dissolution, diffusion, group condensation, and solidification. The Na in the solidified structure is used to balance the charge of [AlO4]. + , K + Alkali metal ions can efficiently replace and adsorb cationic (group) pollutants in sewage.
[0003] Silver pyrosilicate (Ag6Si2O7) has excellent photocatalytic performance, but it is susceptible to photocorrosion, which prevents it from fully exerting its performance. At the same time, the single-structured bulk photocatalyst is easy to agglomerate, making it difficult to recycle, and it is also impossible to effectively control the macroscopic pore channels, resulting in less exposed interfaces for the adsorbent, and the internal materials cannot be effectively used, which seriously limits its actual promotion and application in the energy and environmental fields.
[0004] Therefore, improving the service stability of silver pyrosilicate photocatalysts, improving the structure of bulk silver pyrosilicate photocatalysts, and improving their catalytic performance are of great significance for their promotion and application. Summary of the invention
[0005] The purpose of the present invention is to provide a geopolymer / silver disilicate photocatalyst, a heterojunction photocatalyst, a 3D configuration photocatalyst, and a preparation method and application thereof, so as to solve the problem that the existing silver disilicate catalyst cannot fully exert its performance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a geopolymer / silver pyrosilicate photocatalyst, comprising the following steps:
[0008] (1) mixing alkali with silica sol to react and obtain an alkali excitation solution;
[0009] (2) mixing the alkali excitation solution and the aluminosilicate material to obtain a geopolymer precursor sol;
[0010] (3) mixing the geopolymer precursor sol with silver nitrate to obtain a geopolymer / silver disilicate photocatalyst slurry;
[0011] (4) The geopolymer / silver pyrosilicate photocatalyst slurry is cast, dried and cured to obtain a geopolymer / silver pyrosilicate photocatalyst.
[0012] Preferably, in the above-mentioned method for preparing the geopolymer / silver disilicate photocatalyst, the base in step (1) is one or more of lithium hydroxide, sodium hydroxide and potassium hydroxide;
[0013] The silica sol in step (1) is alkaline silica sol or neutral silica sol;
[0014] The aluminosilicate material in step (2) includes but is not limited to one or more of metakaolin, fly ash, slag, tailings and waste glass;
[0015] The molar ratio of Si to Al in the geopolymer precursor sol in step (2) is 0.5:1 to 3:1;
[0016] The molar ratio of Al to alkali metal elements in the geopolymer precursor sol in step (2) is 1:1;
[0017] The molar ratio of Si to Ag in the geopolymer / silver disilicate photocatalyst slurry in step (3) is 1:5 to 7:5;
[0018] The reaction temperature in step (1) is less than 5°C and the reaction time is 30 to 60 minutes;
[0019] The mixing temperature in step (2) and step (3) is independently <5°C, and the mixing time in step (2) and step (3) is independently 30 to 60 minutes.
[0020] The invention also provides a geopolymer / silver disilicate photocatalyst prepared by a preparation method of the geopolymer / silver disilicate photocatalyst.
[0021] The present invention also provides a method for preparing a geopolymer / silver disilicate heterojunction photocatalyst, comprising the following steps:
[0022] The aforementioned geopolymer precursor sol, silver nitrate and heterojunction compatible semiconductor are mixed to obtain a geopolymer / silver disilicate heterojunction photocatalyst slurry, and then the geopolymer / silver disilicate heterojunction photocatalyst is obtained through casting, drying and curing.
[0023] Preferably, in the above-mentioned method for preparing the geopolymer / silver disilicate heterojunction photocatalyst, the heterojunction adaptive semiconductor is a Z-type heterojunction adaptive semiconductor, a II-type heterojunction adaptive semiconductor, an S-type heterojunction adaptive semiconductor or a I-type heterojunction adaptive semiconductor;
[0024] The Z-type heterojunction compatible semiconductor includes but is not limited to AgI, Bi2S3, Bi2O2CO3, ZnIn2S4, g-C3N4, BiVO4, Bi2WO6 or α-Fe2O3;
[0025] The type II heterojunction compatible semiconductor includes but is not limited to Bi2Sn2O7 or CuO;
[0026] The S-type heterojunction compatible semiconductor includes but is not limited to Ag2WO4 or CaSnO3;
[0027] The type I heterojunction compatible semiconductor includes but is not limited to ZnS;
[0028] The molar ratio of Si to Ag in the geopolymer / silver disilicate heterojunction photocatalyst slurry is 1:5 to 7:5;
[0029] The molar ratio of silver pyrosilicate to heterojunction compatible semiconductor in the geopolymer / silver pyrosilicate heterojunction photocatalyst slurry is 1:1 to 10:1;
[0030] The mixing temperature is less than 5°C, and the mixing time is 30 to 60 minutes.
[0031] The invention also provides a geopolymer / silver disilicate heterojunction photocatalyst prepared by a preparation method of the geopolymer / silver disilicate heterojunction photocatalyst.
[0032] The present invention also provides a method for preparing a geopolymer / silver disilicate 3D configuration photocatalyst, comprising the following steps:
[0033] The above-mentioned geopolymer / silver disilicate photocatalyst slurry or geopolymer / silver disilicate heterojunction photocatalyst slurry is subjected to direct writing 3D printing to obtain a geopolymer / silver disilicate 3D configuration photocatalyst wet blank;
[0034] or,
[0035] The geopolymer / silver disilicate photocatalyst slurry or the geopolymer / silver disilicate heterojunction photocatalyst slurry is mixed with a foaming agent, and a geopolymer / silver disilicate 3D configuration photocatalyst foaming wet blank is obtained by direct writing 3D printing;
[0036] The geopolymer / silver disilicate 3D configuration photocatalyst wet billet or the geopolymer / silver disilicate 3D configuration photocatalyst foamed wet billet is dried and cured to obtain the geopolymer / silver disilicate 3D configuration photocatalyst.
[0037] Preferably, in the method for preparing the above-mentioned geopolymer / silver disilicate 3D configuration photocatalyst, the foaming agent includes but is not limited to H2O2 or aluminum powder;
[0038] The mass of the foaming agent is 0.5-5% of the mass of the geopolymer / silver disilicate photocatalyst slurry or the geopolymer / silver disilicate heterojunction photocatalyst slurry;
[0039] The mixing temperature is less than 5°C, and the mixing time is 30 to 60 minutes.
[0040] The invention also provides a geopolymer / silver disilicate 3D configuration photocatalyst prepared by a preparation method of the geopolymer / silver disilicate 3D configuration photocatalyst.
[0041] The present invention also provides the use of geopolymer / silver disilicate photocatalyst, geopolymer / silver disilicate heterojunction photocatalyst or geopolymer / silver disilicate 3D configuration photocatalyst in wastewater treatment, air purification, sterilization or CO2 reduction.
[0042] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The present invention improves the photocatalytic performance of silver disilicate (Ag6Si2O7) in a simple and mild manner by composite geopolymer. Geopolymer, as a new type of adsorbent, has the characteristics of wide raw material sources, low production cost and excellent performance, and is considered to be a green and environmentally friendly material. The present invention synthesizes Ag6Si2O7 in situ in a geopolymer precursor and composites the geopolymer with Ag6Si2O7 to obtain a photocatalytic material with better performance than the two.
[0044] (2) The present invention provides a method for preparing a geopolymer / silver disilicate photocatalyst and a heterojunction photocatalyst in situ by a coprecipitation method, and a 3D-configured geopolymer / silver disilicate photocatalyst by direct writing 3D printing technology. A geopolymer / silver disilicate photocatalyst with a heterojunction is prepared in situ by a coprecipitation method under a very mild environment, thereby improving its photocatalytic performance; a three-dimensional model with a complex macroscopic pore structure is designed by a computer, and a geopolymer / silver disilicate 3D-configured photocatalyst with a good pore structure is printed by direct writing 3D printing technology, thereby improving the recovery efficiency of the photocatalyst after use. At the same time, the geopolymer / silver disilicate 3D-configured photocatalyst achieves multi-dimensional expansion of mass transfer and light transmission channels, improves photocatalytic performance, cycle stability and recovery efficiency, and gives full play to the effectiveness of the photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0046] Figure 1The SEM image and mapping image of the geopolymer / silver disilicate photocatalyst in Example 1; wherein A is the SEM image, B is the mapping image of Ag, C is the mapping image of Si, D is the mapping image of O, E is the mapping image of Al, and F is the mapping image of Na;
[0047] Figure 2 This is the adsorption-degradation diagram of tetracycline hydrochloride by the geopolymer / silver pyrosilicate photocatalyst in Example 1;
[0048] Figure 3 This is the adsorption-degradation diagram of tetracycline hydrochloride by the geopolymer / silver disilicate heterojunction photocatalyst in Example 2;
[0049] Figure 4 This is a physical picture of the geopolymer / silver disilicate 3D configuration photocatalyst in Example 3. DETAILED DESCRIPTION
[0050] The present invention provides a method for preparing a geopolymer / silver pyrosilicate photocatalyst, comprising the following steps:
[0051] (1) mixing alkali with silica sol to react and obtain an alkali excitation solution;
[0052] (2) mixing the alkali excitation solution and the aluminosilicate material to obtain a geopolymer precursor sol;
[0053] (3) mixing the geopolymer precursor sol with silver nitrate to obtain a geopolymer / silver disilicate photocatalyst slurry;
[0054] (4) The geopolymer / silver pyrosilicate photocatalyst slurry is cast, dried and cured to obtain a geopolymer / silver pyrosilicate photocatalyst.
[0055] In the present invention, the base in step (1) is preferably one or more of lithium hydroxide, sodium hydroxide and potassium hydroxide, more preferably one or both of lithium hydroxide and sodium hydroxide, and more preferably sodium hydroxide.
[0056] In the present invention, the silica sol in step (1) is preferably alkaline silica sol or neutral silica sol, more preferably neutral silica sol.
[0057] In the present invention, the mass fraction of SiO2 in the silica sol in step (1) is preferably 30-50%, more preferably 35-45%, and more preferably 40%.
[0058] In the present invention, the reaction temperature in step (1) is preferably <5°C, more preferably 0-4°C, and more preferably 0°C; the reaction time is preferably 30-60 min, more preferably 30-50 min, and more preferably 30 min.
[0059] In the present invention, the aluminosilicate material in step (2) includes but is not limited to one or more of metakaolin, fly ash, slag, tailings and waste glass, more preferably one or more of metakaolin, fly ash and slag, more preferably one or both of metakaolin and fly ash.
[0060] In the present invention, the molar ratio of Si to Al in the geopolymer precursor sol in step (2) is preferably 0.5:1-3:1, more preferably 1:1-2.5:1, and more preferably 2:1.
[0061] In the present invention, the molar ratio of Al to alkali metal elements in the geopolymer precursor sol in step (2) is preferably 1:1.
[0062] In the present invention, the molar ratio of Si to Ag in the geopolymer / silver disilicate photocatalyst slurry in step (3) is preferably 1:5-7:5, more preferably 2:5-6:5, and even more preferably 3:5-4:5.
[0063] In the present invention, the temperature of the mixing in step (2) and step (3) is independently preferably <5°C, more preferably 0-4°C, and more preferably 0°C; the time of the mixing in step (2) and step (3) is independently preferably 30-60 min, more preferably 35-50 min, and more preferably 40-45 min.
[0064] In the present invention, the drying temperature in step (4) is preferably 40-80°C, more preferably 50-70°C, and even more preferably 55-65°C.
[0065] In the present invention, the curing temperature in step (4) is preferably 40-80°C, more preferably 45-75°C, and more preferably 60°C; the curing time is preferably 1-7 days, more preferably 2-5 days, and more preferably 3-4 days.
[0066] In the present invention, after the curing in step (4) is completed, it also includes: crushing and screening.
[0067] The invention also provides a geopolymer / silver disilicate photocatalyst prepared by a method for preparing the geopolymer / silver disilicate photocatalyst.
[0068] The present invention also provides a method for preparing a geopolymer / silver disilicate heterojunction photocatalyst, comprising the following steps:
[0069] The aforementioned geopolymer precursor sol, silver nitrate and heterojunction compatible semiconductor are mixed to obtain a geopolymer / silver disilicate heterojunction photocatalyst slurry, and then the geopolymer / silver disilicate heterojunction photocatalyst is obtained through casting, drying and curing.
[0070] In the present invention, the heterojunction adaptor semiconductor is preferably a Z-type heterojunction adaptor semiconductor, a II-type heterojunction adaptor semiconductor, an S-type heterojunction adaptor semiconductor or an I-type heterojunction adaptor semiconductor, further preferably a Z-type heterojunction adaptor semiconductor, a II-type heterojunction adaptor semiconductor or an S-type heterojunction adaptor semiconductor, more preferably a Z-type heterojunction adaptor semiconductor or a II-type heterojunction adaptor semiconductor.
[0071] In the present invention, the Z-type heterojunction adapter semiconductor includes but is not limited to AgI, Bi2S3, Bi2O2CO3, ZnIn2S4, g-C3N4, BiVO4, Bi2WO6 or α-Fe2O3, further preferably AgI, Bi2S3, Bi2O2CO3, ZnIn2S4 or g-C3N4, and more preferably Bi2O2CO3, ZnIn2S4 or g-C3N4.
[0072] In the present invention, the type II heterojunction compatible semiconductor includes but is not limited to Bi2Sn2O7 or CuO, more preferably CuO.
[0073] In the present invention, the S-type heterojunction compatible semiconductor includes but is not limited to Ag2WO4 or CaSnO3, more preferably CaSnO3.
[0074] In the present invention, the type I heterojunction compatible semiconductor includes but is not limited to ZnS.
[0075] In the present invention, the molar ratio of Si to Ag in the geopolymer / silver disilicate heterojunction photocatalyst slurry is preferably 1:5-7:5, more preferably 2:5-6:5, and more preferably 3:5-4:5.
[0076] In the present invention, the molar ratio of silver disilicate to heterojunction compatible semiconductor in the geopolymer / silver disilicate heterojunction photocatalyst slurry is preferably 1:1-10:1, more preferably 2:1-8:1, and more preferably 4:1-6:1.
[0077] In the present invention, the mixing temperature is preferably <5°C, more preferably 0-4°C, and more preferably 0°C; the mixing time is preferably 30-60 min, more preferably 35-50 min, and more preferably 40-45 min.
[0078] In the present invention, the drying temperature is preferably 40 to 80°C, more preferably 50 to 70°C, and even more preferably 55 to 65°C.
[0079] In the present invention, the curing temperature is preferably 40-80°C, more preferably 45-75°C, and more preferably 60°C; the curing time is preferably 1-7 days, more preferably 2-5 days, and more preferably 3-4 days.
[0080] In the present invention, after the curing is completed, the process further includes: crushing and screening.
[0081] The invention also provides a geopolymer / silver disilicate heterojunction photocatalyst prepared by a preparation method of the geopolymer / silver disilicate heterojunction photocatalyst.
[0082] The present invention also provides a method for preparing a geopolymer / silver disilicate 3D configuration photocatalyst, comprising the following steps:
[0083] The aforementioned geopolymer / silver disilicate photocatalyst slurry or the aforementioned geopolymer / silver disilicate heterojunction photocatalyst slurry is subjected to direct writing 3D printing to obtain a geopolymer / silver disilicate 3D configuration photocatalyst wet blank;
[0084] or,
[0085] The geopolymer / silver disilicate photocatalyst slurry or the geopolymer / silver disilicate heterojunction photocatalyst slurry is mixed with a foaming agent, and a geopolymer / silver disilicate 3D configuration photocatalyst foaming wet blank is obtained by direct writing 3D printing;
[0086] The geopolymer / silver disilicate 3D configuration photocatalyst wet billet or the geopolymer / silver disilicate 3D configuration photocatalyst foamed wet billet is dried and cured to obtain the geopolymer / silver disilicate 3D configuration photocatalyst.
[0087] In the present invention, the foaming agent includes but is not limited to H2O2 or aluminum powder, more preferably H2O2.
[0088] In the present invention, the mass of the foaming agent is preferably 0.5-5% of the mass of the geopolymer / silver disilicate photocatalyst slurry or the geopolymer / silver disilicate heterojunction photocatalyst slurry, more preferably 1-4%, and more preferably 2-3%.
[0089] In the present invention, the needle diameter of the direct writing 3D printing is preferably 0.6 mm.
[0090] In the present invention, the mixing temperature is preferably <5°C, more preferably 0-4°C, and more preferably 0°C; the mixing time is 30-60 min, more preferably 35-50 min, and more preferably 40-45 min.
[0091] In the present invention, the drying temperature is preferably 40 to 80°C, more preferably 50 to 70°C, and even more preferably 55 to 65°C.
[0092] In the present invention, the curing temperature is preferably 40-80°C, more preferably 45-75°C, and more preferably 60°C; the curing time is preferably 1-7 days, more preferably 2-5 days, and more preferably 3-4 days.
[0093] In the present invention, the 3D configuration of the geopolymer / silver disilicate 3D configuration photocatalyst is preferably a hexagonal honeycomb, a square spiral structure, a circular spiral structure, a framework structure or a framework sieve structure, further preferably a hexagonal honeycomb, a framework structure or a framework sieve structure, and more preferably a framework sieve structure.
[0094] The invention also provides a geopolymer / silver disilicate 3D configuration photocatalyst prepared by a preparation method of the geopolymer / silver disilicate 3D configuration photocatalyst.
[0095] The present invention also provides the use of geopolymer / silver disilicate photocatalyst, geopolymer / silver disilicate heterojunction photocatalyst or geopolymer / silver disilicate 3D configuration photocatalyst in wastewater treatment, air purification, sterilization or CO2 reduction.
[0096] In the present invention, the CO2 reduction is CO2 photoreduction or CO2 photothermal reduction.
[0097] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0098] Example 1
[0099] The present invention provides a method for preparing a geopolymer / silver pyrosilicate photocatalyst, comprising the following steps:
[0100] (1) Stirring sodium hydroxide and silica sol in an ice water bath at 0°C for 30 minutes to obtain an alkaline excitation solution; wherein the silica sol is a neutral silica sol, and the mass fraction of SiO2 in the silica sol is 40%;
[0101] (2) mixing the alkaline excitation solution with kaolin to obtain a solid-liquid mixture, mechanically stirring the solid-liquid mixture at 0° C. for 60 minutes under ultrasonic action to obtain a geopolymer precursor sol; wherein the molar ratio of Si to Al in the geopolymer precursor sol is 2:1, and the molar ratio of Al to Na in the geopolymer precursor sol is 1:1;
[0102] (3) mixing the geopolymer precursor sol with silver nitrate, and mechanically stirring at 0°C for 40 minutes to obtain a geopolymer / silver disilicate photocatalyst slurry; wherein the molar ratio of Si to Ag in the geopolymer / silver disilicate photocatalyst slurry is 2:5;
[0103] (4) The geopolymer / silver pyrosilicate photocatalyst slurry was poured into a silicone mold to obtain a solidified block, which was then placed in an oven for constant temperature drying at 50°C, and then cured at 50°C for 5 days. Finally, the geopolymer / silver pyrosilicate photocatalyst was obtained by crushing and screening.
[0104] The SEM image and mapping image of the geopolymer / silver disilicate photocatalyst prepared above are as follows: Figure 1 As shown. Figure 1 It can be seen that geopolymer / silver disilicate photocatalyst with homogeneous element distribution can be synthesized by in situ co-precipitation.
[0105] The tetracycline hydrochloride degradation test was carried out on the geopolymer / silver pyrosilicate photocatalyst prepared above. Specifically, the adsorption-degradation test of tetracycline hydrochloride was carried out under different input amounts of the geopolymer / silver pyrosilicate photocatalyst prepared above, the concentration of the tetracycline hydrochloride solution used was 10 mg / L, the volume of the tetracycline hydrochloride solution used was 100 mL, and the residual amount of tetracycline hydrochloride was tested by a spectrophotometer. The removal effect of different geopolymer / silver pyrosilicate photocatalyst input amounts is as follows: Figure 2 shown.
[0106] The results showed that within 120 minutes, when the input amount was 0.1g, the removal rate of tetracycline hydrochloride reached 97%. When the input amount was 0.05g, tetracycline could not be degraded in time due to the low input effective ingredients. When the input amount increased to 0.15g, the degradation effect was poor due to the excessive catalyst shielding the light source.
[0107] Example 2
[0108] The present invention provides a method for preparing a geopolymer / silver disilicate heterojunction photocatalyst, comprising the following steps:
[0109] (1) Stirring sodium hydroxide and silica sol in an ice water bath at 0°C for 30 minutes to obtain an alkaline excitation solution; wherein the silica sol is a neutral silica sol, and the mass fraction of SiO2 in the silica sol is 40%;
[0110] (2) mixing the alkaline excitation solution with kaolin to obtain a solid-liquid mixture, mechanically stirring the solid-liquid mixture at 0° C. for 60 minutes under ultrasonic action to obtain a geopolymer precursor sol; wherein the molar ratio of Si to Al in the geopolymer precursor sol is 2:1, and the molar ratio of Al to Na in the geopolymer precursor sol is 1:1;
[0111] (3) mixing the geopolymer precursor sol, silver nitrate and g-C3N4, and mechanically stirring at 0°C for 40 minutes to obtain a geopolymer / silver disilicate heterojunction photocatalyst slurry; wherein the molar ratio of Si to Ag in the geopolymer / silver disilicate heterojunction photocatalyst slurry is 2:5; and the molar ratio of silver disilicate to g-C3N4 in the geopolymer / silver disilicate heterojunction photocatalyst slurry is 5:1;
[0112] (4) The geopolymer / silver disilicate photocatalyst slurry was poured into a silica gel mold to obtain a film-like body, which was then placed in an oven for constant temperature drying at 50°C, and then cured at 50°C for 5 days. Finally, the geopolymer / silver disilicate heterojunction photocatalyst was obtained by crushing and screening.
[0113] The tetracycline hydrochloride degradation test was performed on the geopolymer / silver pyrosilicate heterojunction photocatalyst prepared above. Specifically, the adsorption-degradation test of tetracycline hydrochloride was performed using the geopolymer / silver pyrosilicate heterojunction photocatalyst prepared above, the concentration of the tetracycline hydrochloride solution used was 10 mg / L, the volume of the tetracycline hydrochloride solution used was 100 mL, and the residual amount of tetracycline hydrochloride was tested using a spectrophotometer. The removal effect of tetracycline hydrochloride was as follows: Figure 3 shown.
[0114] The results showed that within 120 minutes, the removal rate of tetracycline hydrochloride reached 96.7%.
[0115] Example 3
[0116] The present invention provides a method for preparing a geopolymer / silver disilicate 3D configuration photocatalyst, comprising the following steps:
[0117] (1) stirring sodium hydroxide and silica sol in an ice water bath at 0°C for 30 minutes to obtain an alkaline excitation solution; wherein the silica sol is a neutral silica sol with a mass fraction of SiO2 of 40%;
[0118] (2) mixing the alkaline excitation solution with kaolin to obtain a solid-liquid mixture, mechanically stirring the solid-liquid mixture at 0° C. for 60 minutes under ultrasonic action to obtain a geopolymer precursor sol; wherein the molar ratio of Si to Al in the geopolymer precursor sol is 2:1, and the molar ratio of Al to Na in the geopolymer precursor sol is 1:1;
[0119] (3) mixing the geopolymer precursor sol, silver nitrate and g-C3N4, and mechanically stirring at 0°C for 40 minutes to obtain a geopolymer / silver pyrosilicate heterojunction photocatalyst slurry; wherein the molar ratio of Si to Ag in the geopolymer / silver pyrosilicate heterojunction photocatalyst slurry is 2:5, and the molar ratio of silver pyrosilicate to g-C3N4 in the geopolymer / silver pyrosilicate heterojunction photocatalyst slurry is 5:1;
[0120] (4) The geopolymer / silver disilicate photocatalyst slurry is subjected to direct writing 3D printing to obtain a 3D geopolymer / silver disilicate 3D photocatalyst wet blank, which is then placed in an oven for constant temperature drying at 50°C, and then cured at 50°C for 5 days to obtain a geopolymer / silver disilicate 3D photocatalyst; wherein the needle diameter of the direct writing 3D printing is 0.6 mm, and the size of the geopolymer / silver disilicate 3D photocatalyst is 10 mm×10 mm×3.6 mm.
[0121] The physical picture of the geopolymer / silver disilicate 3D configuration photocatalyst prepared as above is as follows Figure 4 As shown. Figure 4 It can be seen that the geopolymer / silver disilicate 3D configuration photocatalyst prepared above is a frame sieve structure.
[0122] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a geopolymer / silver disilicate photocatalyst, characterized in that: The following steps are involved: (1) mixing alkali and silica sol to react to obtain an alkali excitation solution; (2) mixing the alkali excitation solution and the aluminosilicate material to obtain a geopolymer precursor sol; (3) mixing the geopolymer precursor sol with silver nitrate to obtain a geopolymer / silver disilicate photocatalyst slurry; (4) casting, drying and curing the geopolymer / silver pyrosilicate photocatalyst slurry to obtain a geopolymer / silver pyrosilicate photocatalyst; The molar ratio of Si to Ag in the geopolymer / silver disilicate photocatalyst slurry in step (3) is 2:
5.
2. The method for preparing the geopolymer / silver disilicate photocatalyst according to claim 1, characterized in that: The base in step (1) is one or more of lithium hydroxide, sodium hydroxide and potassium hydroxide; The silica sol in step (1) is alkaline silica sol or neutral silica sol; The aluminosilicate material in step (2) includes but is not limited to one or more of metakaolin, fly ash, slag, tailings and waste glass; The molar ratio of Si to Al in the geopolymer precursor sol in step (2) is 0.5:1 to 3:1; The molar ratio of Al to alkali metal elements in the geopolymer precursor sol in step (2) is 1:1; The reaction temperature in step (1) is less than 5°C and the reaction time is 30 to 60 minutes; The mixing temperature in step (2) and step (3) is independently <5°C, and the mixing time in step (2) and step (3) is independently 30 to 60 minutes.
3. The geopolymer / silver disilicate photocatalyst prepared by the method for preparing the geopolymer / silver disilicate photocatalyst according to claim 1 or 2.
4. A method for preparing a geopolymer / silver disilicate heterojunction photocatalyst, characterized in that: The following steps are involved: The geopolymer precursor sol, silver nitrate and heterojunction compatible semiconductor in the preparation method of claim 1 are mixed to obtain a geopolymer / silver disilicate heterojunction photocatalyst slurry, and then the geopolymer / silver disilicate heterojunction photocatalyst is obtained by casting, drying and curing.
5. The method for preparing the geopolymer / silver disilicate heterojunction photocatalyst according to claim 4, characterized in that: The heterojunction adapted semiconductor is a Z-type heterojunction adapted semiconductor, a II-type heterojunction adapted semiconductor, an S-type heterojunction adapted semiconductor or a I-type heterojunction adapted semiconductor; The Z-type heterojunction compatible semiconductor includes but is not limited to AgI, Bi2S3, Bi2O2CO3, ZnIn2S4, g-C3N4, BiVO4, Bi2WO6 or α-Fe2O3; The type II heterojunction compatible semiconductor includes but is not limited to Bi2Sn2O7 or CuO; The S-type heterojunction compatible semiconductor includes but is not limited to Ag2WO4 or CaSnO3; The type I heterojunction compatible semiconductor includes but is not limited to ZnS; The molar ratio of Si to Ag in the geopolymer / silver disilicate heterojunction photocatalyst slurry is 1:5 to 7:5; The molar ratio of silver disilicate to heterojunction-compatible semiconductor in the geopolymer / silver disilicate heterojunction photocatalyst slurry is 1:1 to 10:1; The mixing temperature is less than 5° C., and the mixing time is 30 to 60 minutes.
6. The geopolymer / silver disilicate heterojunction photocatalyst prepared by the preparation method of the geopolymer / silver disilicate heterojunction photocatalyst according to claim 4 or 5.
7. A method for preparing a geopolymer / silver disilicate 3D configuration photocatalyst, characterized in that: The following steps are involved: The geopolymer / silver disilicate photocatalyst slurry in the preparation method of claim 1 or the geopolymer / silver disilicate heterojunction photocatalyst slurry in the preparation method of claim 4 is subjected to direct writing 3D printing to obtain a geopolymer / silver disilicate 3D configuration photocatalyst wet blank; or, The geopolymer / silver disilicate photocatalyst slurry in the preparation method of claim 1 or the geopolymer / silver disilicate heterojunction photocatalyst slurry in the preparation method of claim 4 is mixed with a foaming agent, and a geopolymer / silver disilicate 3D configuration photocatalyst foaming wet blank is obtained by direct writing 3D printing; The geopolymer / silver disilicate 3D configuration photocatalyst wet billet or the geopolymer / silver disilicate 3D configuration photocatalyst foamed wet billet is dried and cured to obtain the geopolymer / silver disilicate 3D configuration photocatalyst.
8. The method for preparing the geopolymer / silver disilicate 3D configuration photocatalyst according to claim 7, characterized in that: The foaming agent includes but is not limited to H2O2 or aluminum powder; The mass of the foaming agent is 0.5-5% of the mass of the geopolymer / silver disilicate photocatalyst slurry or the geopolymer / silver disilicate heterojunction photocatalyst slurry; The mixing temperature is less than 5° C., and the mixing time is 30 to 60 minutes.
9. The geopolymer / silver disilicate 3D configuration photocatalyst prepared by the preparation method of the geopolymer / silver disilicate 3D configuration photocatalyst according to claim 7 or 8.
10. Use of the geopolymer / silver disilicate photocatalyst according to claim 3, the geopolymer / silver disilicate heterojunction photocatalyst according to claim 6, or the geopolymer / silver disilicate 3D configuration photocatalyst according to claim 9 in wastewater treatment, air purification, sterilization or CO2 reduction.
Citation Information
Patent Citations
Silver pyrosilicate / carbon nanotube visible light catalyst and preparation method thereof
CN109126783A
Modified geopolymer and modified geopolymer composite and process for the production thereof
CN109641798A
Cited By
Method for in-situ synthesis of visible light photocatalytic geopolymer by using vanadium-containing solid waste
CN122076421A